2017
DOI: 10.3389/fpls.2017.00514
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Proteomic Analysis of Brassinosteroid-induced Protein Phosphorylation in Rice (Oryza sativa L.)

Abstract: The group of polyhydroxysteroid phytohormones referred to as the brassinosteroids (BRs) is known to act on plant development and the stress response. BR signal transduction relies largely on protein phosphorylation. By employing a label-free, MS (Mass Spectrometry)-based phosphoproteomic approach, we report here the largest profiling of 4,034 phosphosites on 1,900 phosphoproteins from rice young seedlings and their dynamic response to BR. 1,821 proteins, including kinases, transcription factors and core compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 81 publications
1
19
0
Order By: Relevance
“…Quantitative RT-PCR was performed as described by Hou et al (2017) [ 63 ]. Briefly, four micrograms of total RNA was applied for reverse transcription using first strand cDNA synthesis Kit (Toyobo, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative RT-PCR was performed as described by Hou et al (2017) [ 63 ]. Briefly, four micrograms of total RNA was applied for reverse transcription using first strand cDNA synthesis Kit (Toyobo, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Though high-throughput phosphoproteomic studies of plant species other than Arabidopsis are to date uncommon, available studies have found evidence for phosphorylation of the canonical rice Gα, RGA1, at S10 [183] and S110 [173,184186]. Multiple phosphosites were also identified for an XLG in rice, encoded by the gene Os06t0111400.…”
Section: G Protein Subunit Phosphorylation In Plant Systemsmentioning
confidence: 99%
“…Multiple phosphosites were also identified for an XLG in rice, encoded by the gene Os06t0111400. These rice XLG phosphosites span the protein from the N-terminal domain (S68 [183], S183 [173,183,184], and Y186 [173]) to the Gα-like domain (T669 [184], which is proximal to the G3 motif) to the C-terminal extension that we suggested above to be a potential phosphorylation hotspot (S859/S860/S861 — the exact site could not be conclusively attributed within these three consecutive serines [173]).…”
Section: G Protein Subunit Phosphorylation In Plant Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Technological developments in phosphoproteomics now offer novel opportunities to identify phosphosites more globally. Thus, large scale scans of induced phosphoproteins have been carried out with a view to characterizing the plant response to drought [ 22 ], exogenous hormone treatment [ 23 , 24 ], salinity [ 25 ] and high temperature [ 26 ], although not as yet to heavy metal exposure. The current paper presents a comprehensive analysis of phosphorylation induced in rice seedlings by their exposure to Cd, conducted using an iTRAQ (isobaric tag for relative and absolute quantitation) based quantitative phosphoproteomic approach.…”
Section: Introductionmentioning
confidence: 99%